2010
DOI: 10.1017/s1368980010002545
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a participatory agriculture and nutrition education project on child growth in northern Malawi

Abstract: Long-term efforts to improve child nutrition through participatory agricultural interventions had a significant effect on child growth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 98 publications
(58 citation statements)
references
References 24 publications
1
57
0
Order By: Relevance
“…The SFHC project integrates sustainable agriculture and nutrition using a participatory approach to improve child nutrition, in which farming households develop and test different strategies, including crop diversification, organic methods, and nutrition education [50]. Previous studies found evidence that SFHC participating households improved their food security, nutrition and ecosystem services [5153]. …”
Section: Introductionmentioning
confidence: 99%
“…The SFHC project integrates sustainable agriculture and nutrition using a participatory approach to improve child nutrition, in which farming households develop and test different strategies, including crop diversification, organic methods, and nutrition education [50]. Previous studies found evidence that SFHC participating households improved their food security, nutrition and ecosystem services [5153]. …”
Section: Introductionmentioning
confidence: 99%
“…A diverse diet has positive impacts on child nutritional status and other health outcomes in children, although there are counter examples (Arimond et al 2010;Berti and Jones 2013;Bezner Kerr et al 2011). In this context, there is need for studies exploring the role of agricultural subsidies, and crops grown, on household food consumption.…”
Section: Introductionmentioning
confidence: 99%
“…Our review identified only one study -on a participatory agriculture programme in Malawi (Bezner-Kerr et al 2010) -that assessed the effects of agricultural practice innovations on food security. It was unable to identify any effects of the programme.…”
Section: Effects On Food Securitymentioning
confidence: 99%